RELIABILITY OF TELE-ASSESSMENT OF PERFORMANCE-BASED TESTS IN PATIENTS WITH KNEE OSTEOARTHRITIS. - Özsoy, Gülşah; Yılmaz, Hayriye; Doğan, Nesibe (Karya Journal of Health Science, 2025)
Objective: Knee osteoarthritis (OA) is one of the primary causes of disability, significantly impacting daily activities and quality of life. In recent years, tele-assessment methods have gained importance as effective tools for assessing physical performance, particularly for patients who face challenges in accessing in-person healthcare services. This study aimed to assess the intra- and inter-rater reliability of three commonly used performance-based tests - Timed Up and Go Test (TUG), Single Leg Stance Test (SLS), and Thirty-Second Chair Stand Test (30CST) - when applied in tele-assessment settings. Method: A methodological study was conducted with 60 participants diagnosed with Grade 2-3 knee OA according to the Kellgren and Lawrence scale. Participants completed the TUG, SLS, and 30CST under two conditions: face-to-face in a clinical setting and remotely via tele-assessment (synchronized real-time video and asynchronized video recordings). Reliability was evaluated using Intraclass Correlation Coefficients (ICCs), Bland-Altman plots, and statistical measures of variability including Standard Error of Measurement (SEM) and Smallest Detectable Change (SDC). Results: The inter-rater reliability between face-to-face and teleassessment was good-to-excellent for TUG (ICC=0.824), SLS (ICC=0.902), and 30CST (ICC=0.848). Intra-rater reliability for teleassessment was also good-to-excellent for TUG (ICC=0.949), SLS (ICC=0.814), and 30CST (ICC=0.926). Conclusion: The findings indicate that TUG, SLS, and 30CST are reliable tools for tele-assessment in patients with knee OA. These tests can be effectively implemented in home-based telehealth programs to monitor physical performance and guide rehabilitation interventions. Their integration into remote care models may enhance patient engagement and adherence to rehabilitation protocols. Moreover, they provide clinicians with accessible and objective measures to make informed decisions regarding treatment progression.